Distribution of Labour Productivity in Japan over the Period 1996-2006 - Yoshi Fujiwara; Hiroshi Iyetomi; Yuichi Ikeda; Wataru Souma (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
The distribution of labour productivity is investigated by analyzing the longitudinal micro-level data set which contains the detailed financial conditions of large numbers of Japanese companies over the period 1996-2006. The authors show that the distribution of labour productivity in both the high and low productivity ranges follows a power law distribution. The generalized beta function of the second kind, which asymptotically reproduces a power law function, is applied to explain the distribution of labour productivity. By comparing the power law exponents that characterize high and low productivity ranges, the authors show that for manufacturing industries, inequality in the low productivity range is larger than that in the high productivity range. For the manufacturing industries, the authors also clarify that the change of inequality in the low productivity range has strong correlation with GDP. In addition, by comparing the power law exponents of the high productivity range in the manufacturing and non-manufacturing industries, the authors show that the inequality of the non-manufacturing industry is higher than that of the manufacturing industry.
Keywords: C16; E23; L60; 330; Labour productivity; marginal productivity; power law distribution; inequality; Arbeitsproduktivität; Unternehmen; Statistische Verteilung; Japan